2021
DOI: 10.15537/smj.2021.42.6.20210016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of retinopathy and associated risk factors among high- and low-risk patients with type 2 diabetes mellitus

Abstract: Objectives: To assess the prevalence and risk factors of diabetic retinopathy (DR) in patients with type 2 diabetes mellitus (T2DM) of different risks, based on the level of glycated hemoglobin (HbA1c). Methods:A cross-sectional study was conducted in in the chronic illness clinics in Saudi Arabia between January 2019 and February 2020. Data were extracted from 428 T2DM patients' medical records and random sampling were carried out using a ratio of 1:3, matched for gender and duration of DM. Patients with HbA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 12 publications
1
17
2
1
Order By: Relevance
“…The prevalence of DR varies greatly between studies, from 5% to 40% in recent reports 11,14,21–24 . The global prevalence of DR has been estimated at 22% 8 which is lower than the 37% prevalence in our study.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The prevalence of DR varies greatly between studies, from 5% to 40% in recent reports 11,14,21–24 . The global prevalence of DR has been estimated at 22% 8 which is lower than the 37% prevalence in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…The United Kingdom Prospective Diabetes Study (UKPDS) also had a 37% prevalence of any DR at baseline in newly diagnosed Type 2 diabetes 25 and the baseline prevalence in the WESDR was similar at 39% in the older onset group not on insulin even if there was a higher 70% prevalence in the older onset insulin‐treated group 4 . A more recent Saudi Arabian study using data from a chronic illness clinic found a 38% prevalence for any DR in people with Type 2 diabetes, 23 similar to our results. In a 2018 Thai study, 24 a 5% prevalence of DR in people with Type 2 diabetes was lower than in many other studies, likely reflecting the lack of data from university hospitals including tertiary medical centres 24 …”
Section: Discussionmentioning
confidence: 99%
“…Another variable considered of great interest is the association between high levels of glycosylated hemoglobin (HbA1c) and DR. We can see that the median HbA1c levels found in patients with DR was 8.2 mg/dL, while, in the group without DR, it was 7.2 mg/dL. This is associated with the study conducted by Alghamdi et al 3 that describes a prevalence of up to 88% of DR in patients with elevated HbA1c levels. In this last study, they also found a correlation between high levels of low-density lipoproteins and the risk of DR, which is why it is another factor that should be taken into consideration 3 .…”
supporting
confidence: 65%
“…This is associated with the study conducted by Alghamdi et al 3 that describes a prevalence of up to 88% of DR in patients with elevated HbA1c levels. In this last study, they also found a correlation between high levels of low-density lipoproteins and the risk of DR, which is why it is another factor that should be taken into consideration 3 .…”
mentioning
confidence: 71%
“…Vemos que la mediana de HbA1c encontrada en pacientes con RD fue de 8,2 mg/dl, mientras que en el grupo sin RD fue de 7,2 mg/dl. Esto se relaciona con el estudio de Alghamdi et al 3 , que describe una prevalencia de hasta el 88% de RD en pacientes con valores elevados de HbA1c. En este último estudio también encuentran una relación entre niveles altos de lipoproteínas de baja densidad (LDL) y riesgo de RD, por lo que es otro factor que debe tenerse en cuenta 3 .…”
unclassified